Water Disclosure in Indonesian Mining Companies: The Role of Size, Leverage, Market Value, and Growth - Muhammad Azlan Rifai; Poppy Nurmayanti M.; Ulfa Afifah (JURNAL AKUNTANSI DAN AUDITING, 2025)
AbstractThis study investigates the primary drivers behind Corporate Water Disclosure (CWD) within the Indonesian mining sector, analyzing data from 16 IDX-listed companies spanning 2018–2023. Prompted by growing scrutiny over water resource management and corporate sustainability, this research employs a quantitative approach using Eviews13 with panel data regression (Fixed Effect Model) to assess the impact of firm size, leverage, market value, company growth, firm age, and CEO expertise. The analysis determines that all variables, excluding company growth, significantly influence CWD levels. These outcomes support Stakeholder and Signaling theories, highlighting CWD as a vital strategic tool for gaining legitimacy, ensuring regulatory compliance, and building essential stakeholder trust.Keywords: Corporate Water Disclosure, Firm Characteristics, CEO Expertise, Sustainability Reporting, GRI 303, Mining Industry.